Strengthening Urban Health Resilience through the Implementation of the Indonesian Emergency Medical Team (TCK-EMT Indonesia) - Marzun, Muhammad Hakiim; Prasetya, Johan Danu; Paripurno, Eko Teguh; Purwanta, Jaka; Nugroho , Arif Rianto Budi (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2025)
Urban health resilience was increasingly recognized as a critical pillar of sustainable development, particularly in densely populated and disaster-prone cities. As part of the broader framework of urban resilience engineering, strengthening health systems was essential to prevent service disruptions and ensure continuity during crises. Emergency Medical Teams (EMTs) played a central role in this process by providing rapid, standardized, and sustainable responses. However, the Indonesian Emergency Medical Team (TCK-EMT Indonesia) had not yet achieved WHO verification, indicating persistent challenges in governance, operational readiness, and integration with urban health systems. This study applied the Edwards III policy implementation framework, which covered communication, resources, disposition, and bureaucratic structure, through a narrative literature review of national regulations, WHO standards, and After Action Reports from missions in Türkiye (2023) and Myanmar (2025). Findings revealed that although TCK-EMT Indonesia personnel demonstrated strong motivation and adaptive capacity, weaknesses persisted in communication delays, limited logistical self-sufficiency, and fragmented bureaucratic structures. These gaps undermined the ability of urban health systems to sustain essential services during disasters. Comparative insights from Türkiye and Myanmar highlighted how external facilitation, linguistic and cultural barriers, and governance fragilities critically influenced resilience outcomes in urban crisis contexts. The study concluded that strengthening TCK-EMT Indonesia was not only a step toward WHO verification but also a strategic measure for developing adaptive, integrated, and sustainable urban health systems. From the perspective of urban resilience engineering, enhancing EMT capacity constituted a pivotal effort to safeguard disaster-prone cities against increasingly complex health crises.